Pemanfaatan pembelajaran online zoom meeting pada masa pandemi covid-19 - Maulidah, Lailatun Nurul (Maliki Interdisciplinary Journal, 2024)
The benefit of conducting this research is to find out the impact and response of each student who is currently studying at the State Islamic University of Malang in the Education study program towards distance learning using the Zoom Meeting application. Knowing the impact and reaction of each student in the Education study program at the State Islamic University of Malang towards distance learning using the Zoom Meeting application is one of the benefits of conducting this research. The results of this research can also be used to find solutions for implementing ICT in universities for students, in order to ascertain whether distance learning through ICT-based applications can be effective and students at each university can benefit from this in the midst of rampant COVID-19.